Brief Report: Induction of Matrix Metalloproteinase Expression by Synovial Wnt Signaling and Association With Disease Progression in Early Symptomatic Osteoarthritis. Issue 10 (29th August 2017) - van den Bosch, Martijn H.; Blom, Arjen B.; van de Loo, Fons A.; Koenders, Marije I.; Lafeber, Floris P.; van den Berg, Wim B.; van der Kraan, Peter M.; van Lent, Peter L.
Abstract : Objective: Increased Wnt signaling in chondrocytes is associated with development of osteoarthritis (OA). However, OA is considered a disease of the entire joint, where the synovium has been attributed an important role in disease pathogenesis and progression. This study was undertaken to determine whether Wnt signaling in synovial tissue could contribute to pathologic development of OA through the production of matrix metalloproteinases (MMPs), and to assess the relationship of synovial expression of Frizzled ( FZD ) receptors and the Wnt inhibitor FRZB to MMP expression and disease progression in patients with early OA in the Dutch Cohort Hip and Cohort Knee (CHECK) study cohort. Methods: In mouse knee joints, human WNT8A and mouse Wnt16 were overexpressed using adenoviral vectors, and expression of messenger RNA (mRNA) for MMPs in the synovium was determined by reverse transcription–polymerase chain reaction or Luminex assay. In human synovial tissue from a subgroup of patients with early OA with knee pain enrolled in the CHECK cohort, levels of Wnt family members were assessed for linkage to MMP expression and disease progression. In addition, MMP production in human synovium from patients with end‐stage OA was determined after stimulation of Wnt signaling with WNT3A or inhibition with FRZB or DKK1 in the synovium. Results: Overexpression of WNT8A and Wnt16 in mouse knee joints induced MMP expression in vivo. Expression of MMPs relevant to human OA in the synovium from CHECK study participants significantly correlated with expression of FZD1, FZD10, and FRZB mRNA. Moreover, increased FZD1 mRNA expression and decreased FRZB mRNA expression were observed in CHECK study patients who experienced disease progression compared to those who were nonprogressors. Stimulation of human OA synovium with WNT3A induced the production of various MMPs, whereas inhibition of Wnt signaling with FRZB or DKK1 reduced the production of MMPs. Conclusion: Wnt signaling in the synovium may potently induce progression of OA via increased production of MMPs.